2003
DOI: 10.2165/00129784-200303050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation for Patients with Cardiovascular Disease

Abstract: Tobacco use remains the major preventable cause of early mortality and morbidity in the US and is a major risk factor for cardiovascular disease (CVD). Quitting smoking rapidly reduces the risk of cardiovascular events. In this review, we identify and discuss best approaches to assist smoking cessation among patients with CVD. Establishing office systems that reliably identify smokers to healthcare providers is an essential first step. Once the patient is identified as a smoker, providers should inquire about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 86 publications
0
7
0
2
Order By: Relevance
“…In our study, in which the findings are in agreement with those of others, no notable change in blood pressure was documented. 21 Weight gain, which is a common bothersome problem during tobacco withdrawal, 22 was not documented in this study in either group. In a recently published review, bupropion was found to limit postcessation weight gain at the end of treatment but had no long-term effect.…”
Section: Commentmentioning
confidence: 58%
“…In our study, in which the findings are in agreement with those of others, no notable change in blood pressure was documented. 21 Weight gain, which is a common bothersome problem during tobacco withdrawal, 22 was not documented in this study in either group. In a recently published review, bupropion was found to limit postcessation weight gain at the end of treatment but had no long-term effect.…”
Section: Commentmentioning
confidence: 58%
“…Many factors are associated with the continuation of smoking among cardiac patients: younger patient age, higher level of nicotine dependency, lack of future intentions to quit [1], lack of will or confidence, absence of social support [12], belief that “the damage is done,” history of smoking relapse, hostility [13], and absence of smoking cessation advice [10, 14]. Furthermore, Berndt et al [1] distinguished three types of hospitalised cardiac patients according to their smoking characteristics and predictors of smoking abstinence 1 month after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Quit rates among those with cardiovascular disease do not exceed quit rates for the general population. 4 Similarly, about one-third of patients with cancer continue to smoke after diagnosis. 5,6 Understanding why some patients seem to have greater diffi-culty quitting may improve the practice of medicine.…”
Section: Introductionmentioning
confidence: 99%